Emotions in Inter-Action in Environmental Resistances. The case of Comité Salvabosque in Mexico - Poma, Alice; Gravante, Tommaso (PARTECIPAZIONE E CONFLITTO, 2018)
The article analyzes the role of emotions in the experience of a grassroots Mexican group, that is defending an urban forest threated by residential developments. The resistance of this group, started in 2005, is marked by significant place attachment, which has been nurtured and enhanced all along the struggle. The aim of the article is to understand how place attachment is strengthened in urban contexts and why it is a core affective bond for defending the territory. Our hypothesis is that it is a dynamic and mobilizing bond, and its relevance resides in the emotions it generates, which in turn have different effects on the protest. In order to confirm our hypothesis we have analyzed the emotional dimension of the resistances in defense of the forest, through in-depth interviews. The analysis will specifically focus on emotions that strengthen and go together with place attachment.